Institutionalizing documentation for WHO Nigeria country office visibility and improved donor relations, 2013-2016 - Charity Warigon; Wondimagegnehu Alemu; Fiona Braka; Hallah Tashikalmah; Yared Yehushualet; Kulchumi Hammanyero; Samuel Bawa; David Oviaesu; Sisay Tegegne; Mustapha Umar Maiiyali; Anne Eudes Jean Baptiste; Peter Nsubuga; et al. (BMC, 2018)
Abstract Background The mandate and unique experience of the World Health Organization (WHO) globally, enables over 190 countries, Nigeria inclusive, to depend on the technical support provided by the organization to define and mitigate the threats to public health. With other emerging health actors competing for scarce donors' resources, the demand for visibility has invariably equaled expectations on WHO's expertise and technical support. However, the inability to systematically document activities conducted by WHO personnel before 2013 overshadowed most of its invaluable contributions due to poor publicity. The inauguration of the Communications Group in December 2013 with a visibility plan necessitated a paradigm shift towards building a culture of documentation to engender visibility. Methods We used a pre-post design of activities to evaluate the effectiveness of specific interventions implemented to improve visibility from 2013 to 2016. The paper highlights how incorporating communication strategies into the accountability framework of staff contributed in changing the landscape as well as showcasing the activities of WHO in Nigeria for improved donor relations. Results With the specific interventions implemented to improve WHO's visibility in Nigeria, we found that donor relations improved between 2013 and 2015. It is not a mere coincidence that the period corresponds with the era of incorporation of documentation into the accountability framework of technical staff for visibility as locally mobilized resources increased to record 112% in 2013 and 2014. The intervention assisted in the positive projection of WHO and its donors by the Nigeria media. Conclusion Despite several interventions, which worked, made WHO ubiquitous and added awareness and visibility for donors who funded various projects, other factors could have contributed towards achieving results. Notwithstanding, incorporating documentation component into the accountability framework of field staff and clusters has significantly improved communication of WHO's work and promoted healthy competition for increased visibility.